BIIGLE 2.0 - Browsing and Annotating Large Marine Image Collections - Langenkämper, Daniel; Zurowietz, Martin; Schoening, Timm; Nattkemper, Tim W. (Frontiers in Marine Science, 2017)
Combining state-of-the art digital imaging technology with different kinds of marine exploration techniques such as modern autonomous underwater vehicle (AUV), remote operating vehicle (ROV) or other monitoring platforms enables marine imaging on new spatial and/or temporal scales. A comprehensive interpretation of such image collections requires the detection, classification and quantification of objects of interest (OOI) in the images usually performed by domain experts. However, the data volume and the rich content of the images makes the support by software tools inevitable. We define some requirements for marine image annotation and present our new online tool BIIGLE 2.0. It is developed with a special focus on annotating benthic fauna in marine image collections with tools customized to increase efficiency and effectiveness in the manual annotation process. The software architecture of the system is described and the special features of BIIGLE 2.0 are illustrated with different use-cases and future developments are discussed.